Intervensi Keperawatan “Peningkatan Tidur“ pada Pasien Gagal Jantung dengan Gangguan Tidur: Laporan Kasus - Agus Joko Purwanto; Elly Nurrachmah; Prima Agustia Nova; Suko Basuki (Jurnal Keperawatan Silampari, 2022)
This study aims to describe nursing interventions to improve sleep in heart failure patients with sleep disorders. This research is a case report of nursing intervention. The results of the study obtained a case report discussing the case of a 65-year-old man with heart failure who had trouble sleeping, was restless and his condition was getting worse. The nursing diagnosis that emerged was sleep disturbance, with the expected outcome: sleep, and the nursing intervention was sleep improvement. In conclusion, the application of nursing interventions to improve sleep results in a better outcome in overcoming the problem of sleep disorders in heart failure patients. Keywords: Heart Failure, Sleep Disorders, Case Reports, Sleep Improvement